Keabsahan Tanda Tangan Elektronik Melalui Platform DocuSign ditinjau dari Hukum Positif di Indonesia - Lydia Evan, Gladys; Syailendra, Moody (UNES Law Review, 2023)
In this era of globalization, Indonesia has created progress in technology that enhances efficiency and effectiveness, namely the presence of electronic signatures. Electronic signatures can replace the conventional handwritten signatures typically placed on paper. The signature placed on paper in an agreement serves as valid evidence. The government-recognized electronic signature in Indonesia is the certified electronic signature. However, the DocuSign platform has not been certified by the Ministry of Communication and Information Technology through the Certificate Authority, leading to various perspectives on the validity of electronic signatures through the DocuSign platform. This research employs normative methods such as literature review, examination of applicable laws, and legal understanding. The validity of electronic signatures is assessed based on the laws in force in Indonesia.